Tuberculous pleural effusions: advances and controversies - Vorster, Morné J.; Allwood, Brian W.; Diacon, Andreas H.; Koegelenberg, Coenraad F. N. (Journal of Thoracic Disease, 2015)
On a global scale, tuberculosis (TB) remains one of the most frequent causes of pleural effusions. Our understanding of the pathogenesis of the disease has evolved and what was once thought to be an effusion as a result of a pure delayed hypersensitivity reaction is now believed to be the consequence of direct infection of the pleural space with a cascade of events including an immunological response. Pulmonary involvement is more common than previously believed and induced sputum, which is grossly underutilised, can be diagnostic in approximately 50%. The gold standard for the diagnosis of tuberculous pleuritis remains the detection of Mycobacterium tuberculosis in pleural fluid, or pleural biopsy specimens, either by microscopy and/or culture, or the histological demonstration of caseating granulomas in the pleura along with acid fast bacilli (AFB). In high burden settings, however, the diagnosis is frequently inferred in patients who present with a lymphocytic predominant exudate and a high adenosine deaminase (ADA) level, which is a valuable adjunct in the diagnostic evaluation. ADA is generally readily accessible, and together with lymphocyte predominance justifies treatment initiation in patients with a high pre-test probability. Still, false-negative and false-positive results remain an issue. When adding closed pleural biopsy to ADA and lymphocyte count, diagnostic accuracy approaches that of thoracoscopy. The role of other biomarkers is less well described. Early pleural drainage may have a role in selected cases, but more research is required to validate its use and to define the subpopulation that may benefit from such interventions.